Peranan Pengadilan Dalam Pelaksanaan Putusan Arbitrase - Muhammad Naufal Hakim (CV. Lenggogeni Data Publishing, 2024)
Business dispute resolution with adjudication process can be resolved by the parties through litigation or dispute resolution before the court. But this model of settlement is not recommended because the parties are very antagouistic (opposing each other) and also takes a long time. So litigation or dispute resolution before the court is pursued solely as a last resort or if settlement through family or peaceful channels does not find a bright spot or a way out (the last resort or ultimatum remedium). Technically, the function of the court or the duty to adjudicate is formulated as